THE INFLUENCE OF SODIUM CHLORIDE ON THE LIME STABILISATION OF A HIGHLY PLASTIC CLAY SOIL - Marbun, Jawali
The strength of a soil subgrade plays an important part in determining the thickness required for a flexible road pavement. If a subgrade consists of a heavy clay which has a low bearing capacity and is susceptible to volume change, its engineering properties may have to be improved. This thesis describes an investigation into the treatment with lime and sodium chloride of a heavy clay from Ujung Berung (PI = 57 % and clay content = 62 7.). For this purpose, several combinations of lime content and sodium chloride content were used. Laboratory tests were performed to investigate the influence of these admixtures on the plasticity, the expansion during saturation and the strength of the soil. Plasticity indices were determined by the Atterberg limit tests; the expansion of the soil was measured as swelling on soaking; and the strength was determined by unconfined compression test. The laboratory test results showed that the addition of sodium chloride to the soil/lime mix increased the liquid limit (LL), decreased the plastic limit (PL) and thus increased the plasticity index (PI). The amount of swelling on soaking increased with increases in the sodium chloride content. These results were obtained for two lime contents tested (i.e 4 and 8 % by weight of dry weight of soil) and for the soil free lime. The addition of small amounts of sodium chloride to the soil/lime mixtures increased the soaked strengths beyond that which would have been produced by an increase of lime content of the same amounts. This effect was only developed for sodium chloride contents of up to 2 percent. For contents greater than this figure a lower strength was achieved. The maximum strength gain, over that for lime stabilisation only with the same total additive content occurred with 1 % of sodium chloride. Using the laboratory test results a simple evaluation base only on the purchase price of lime and sodium chloride, and, neglecting the increased costs which would be incurred by the use of two additives rather than one, showed that for equal soaked strengths the use of lime without sodium chloride provided a cheaper solution and at the same time produced a lower amount of swelling. On engineering and cost factors therefore, no advantage is likely to be gained by the incorporation of sodium chloride in the lime stabilisation of this heavy clay from Ujung Berung .